PENINGKATAN PENGGUNAAN MOBILE JKN MELALUI PROGRAM SIAP JKN (SOSIALISASI, INSTALASI, DAN AKTIVASI PASIEN DI MOBILE JKN) DI RUMAH SAKIT ARTHA BUNDA TAHUN 2025 - Safira, Retno Sofy; Aprilianingsih, Maya; Pertiwi, Windi (Journal of Hospital Administration and Excellent Health Service, 2025)
Introduction: Low utilization of the Mobile JKN application at Artha Bunda Hospital led to long queues, reduced service efficiency, and decreased patient satisfaction. Method: This descriptive qualitative study used observation, interviews, and 5W+1H and USG scoring analysis (Urgency, Seriousness, Growth). Result: Major obstacles include lack of patient education, limited access to smartphones, and low digital literacy. The SIAP JKN program (Socialization, Installation, and Activation) was developed and implemented during the internship, resulting in a significant increase in Mobile JKN usage. Conclusion: The SIAP JKN program effectively improved Mobile JKN coverage and supported service digitalization in hospitals.